The Importance Of Mother’s Weight In Pregnancy With Gestational Diabetes - PhD, Migena PRIFTI; PhD, Brizida Refatllari; Krasniqi, Prof.Marsida; Prof. Floreta Kurti (South Eastern European Journal of Public Health, 2024)
Introduction Gestational diabetes is known as a pathology that appears during pregnancy, accompanied by changes not only in the health of the mother, but also in the growth and intrauterine development of the child from its first weeks. The factors that influence the appearance of this pathology are different. In fact, in the last 10 years, an increase in obesity has been noticed, which is one of the most important in the group of risk factors for diabetes. This increase comes not only from malnutrition but also from the lifestyle and work of women in our country. Objective: The role played by obesity in the occurrence of changes in fast glycaemia levels in pregnant women, predisposed or diagnosed with gestational diabetes. Methodology. After the primary processing of the data obtained from the patients, the pregnant women who had monitored their pregnancy for at least 7 months at least with the body mass index (BMI) and with the fast glycaemi values were selected. The data were processed in 2*2 statistical tables, where the selected number of participants with prediabetes or gestational diabetes was associated with a risk factor: weight, to analyze the respective data in our population. Results. In about 176 patients with GE changes, statistically significant changes were observed in the group with maternal obesity. The number of obese patients in the group that had changes in glycemic levels was 3 times higher. During the second trimester, the entire group that ended the pregnancy within the 22-24th week for fetal reasons, was assessed to have changes in fast glycemic levels, which varied in the values of prediabetes and gestational diabetes. Also, within the same group with DG, women with high BMI have a higher risk of developing various pregnancy complications, especially during the third trimester.